Empowering Families in the Prevention of Tuberculosis Transmission Through Education on Clean and Healthy Living Behavior (PHBS) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Tuberculosis is one of the infectious diseases that is the leading cause of death worldwide. In 2019, Indonesia was ranked 2nd with the highest number of tuberculosis cases in the world. Family is one of the most risky factors in tuberculosis transmission. However, family has crucial role in taking care for family members suffering from tuberculosis because a good care is able to speed up the convalescence and prevent the transmission to other family members. This can be influenced by several factors, such as family’s knowledge and roles. The Community Service activity carried out to family members taking care for people with tuberculosis is one of the strategies to increase knowledge in a Clean and Healthy Living with the aim to reduce the rate of tuberculosis transmission. Based on the results of the evaluation, participants were able to answer questions related to the knowledge material on Clean and Healthy Living Behavior (PHBS), and almost all participants provided correct answer related to hand washing with soap (95%). It is expected that participants as a family taking care for people with tuberculosis can implement the knowledge acquired during health education about PHBS